(untitled) (Journal of Asian Development Studies, 2025)
The present quantitative study enhances research knowledge regarding financial socialisation effects on financial decision-making quality by determining financial self-efficacy as a mediating factor, together with cognitive financial competence as a moderator variable. The study employs the Theory of Planned Behaviour to examine how financial information from families, friends, and educational organisations influences investment choices by increasing confidence levels. Punjab, Pakistan, served as the survey location to gather data from 200 respondents (response rate 61%. Regression and correlation techniques implemented through SPSS demonstrate that financial socialisation leads to effective improvement in self-efficacy, resulting in superior investment choices. Persons whose financial education has reached a cognitive level display higher self confidence because financial socialisation teaches them essential behavioural patterns. Educational institutions should utilise financial education programs that help students develop mastery, in addition to knowledge acquisition, for financial decision-making expertise. This investigation provides evidence for developing standardised financial training programs that yield valuable improvements in current research on the intersection of behavioural finance and financial literacy. Research results help financial institutions, along with educators, create effective education programs to enhance the financial well-being of their participants.